Existence of a Renormalised Solutions for a Class of Nonlinear Degenerated Parabolic Problems with L1 Data (Journal of Partial Differential Equations, 2018)
We study the existence of renormalized solutions for a class of nonlinear degenerated parabolic problem. The Carathéodory function satisfying the coercivity condition, the growth condition and only the large monotonicity. The data belongs to L^1(Ω).
Keywords: Weighted Sobolev spaces; truncations; nonlinear doubling parabolic equation; renormalized solutions